The acquisition of basic job skills in fieldwork approaches to history, ICSS, Malaysia - Salleh, Mohamad Johdi; Ahmad, Abdul Razaq; Zainal Abiddin, Norhasni (Medwell Journals, 2010)
The study is essentially an exploratory survey, which sets out to obtain some concrete information on the knowledge and understanding of and attitudes towards the acquisition of job skills in history fieldwork method among Malaysian secondary schools pupils based on the Integrated Curriculum for Secondary Schools (ICSS). The researcher employed the stratified sampling method and selected two states in Malaysia, namely Perak and Terengganu involving 400 pupils from each state. The finding reveals that a great number of pupils perceived that basic jobs skills are acquired through fieldwork approaches in history, the response of Yes in Perak and Terengganu are almost the same, the highest response of Yes among schools was the science, form four scores the highest with 91.2% responses said Yes, the score among boys and girls were almost the same and the highest score of agreement among ethnic groups was the Malays. Interestingly, it was discovered from the interviewed that history fieldwork was related to professionals such as teacher, administrator, archaeologist, lawyer, surveyor and engineer. It is hoped that the study would raise concern, awareness and benefit to all involved in the teaching and learning of history fieldwork to achieve the objectives of the Malaysian Philosophy of Education which is to fulfil the physical, emotional, intellectual, spiritual and moral development of pupils towards the dissemination of first class human capital in the millennium.